2019
DOI: 10.13189/ujer.2019.071006
|View full text |Cite
|
Sign up to set email alerts
|

Model of Student Character Based on Character Building in Teaching Learning Process

Abstract: The aim of this research is to offer a model for student character on the basis of character building in teaching learning process. The sample group with 450 students represented grades 4-6 from 5 elementary schools in Jakarta. The Structural Equation Modeling (SEM) was used to analyse the data of this research. The findings confirmed that character building in teaching learning process encouraging student character was not supported. Preparation of teaching learning process, the core of teaching learning proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 4 publications
1
27
0
10
Order By: Relevance
“…And loyalty is also influenced by learning through student satisfaction. The student satisfaction was the major driver of student loyalty (Kunanusorn andPuttawong, 2015 andMarini et al, 2019). Weerasinghe and Dedunu (2017) concluded that the quality of academic staff has both direct and indirect impact on students' satisfaction through university image.…”
Section: Student Loyaltymentioning
confidence: 99%
“…And loyalty is also influenced by learning through student satisfaction. The student satisfaction was the major driver of student loyalty (Kunanusorn andPuttawong, 2015 andMarini et al, 2019). Weerasinghe and Dedunu (2017) concluded that the quality of academic staff has both direct and indirect impact on students' satisfaction through university image.…”
Section: Student Loyaltymentioning
confidence: 99%
“…Hasil penelitian Marini A, Maksum A, Satibi O (2019) memberikan kontribusi praktis dengan menunjukkan bahwa pembangunan karakter dalam proses belajar mengajar dapat meningkatkan tingkat karakter mulia siswa dengan menyediakan model untuk karakter siswa. Dengan menggunakan model ini, karakter positif siswa dapat ditingkatkan untuk mencegah penurunan moral siswa (Marini et al, 2019). Sedangkan Wyk (2012) dalam hasil penelitian yang dilaksanakan menyatakan bahwa teknik pembelajaran kooperatif dapat menunjukkan sikap positif siswa serta menunjukkan prestasi yang lebih baik serta memotivasi siswa untuk lebih belajar (Wyk, 2012).…”
Section: Gambar 3 Berani Tampil Dan Terlibat Dalam Kegiatanunclassified
“…This adjustment resulted in an education system concept called Curriculum 2013. There are four competencies that are emphasized in this curriculum, namely spiritual attitudes, social attitudes, skills and knowledge (Novianto and Mustadi, 2015;Marini et al, 2019). Of the four competencies, it can be explained that the purpose of the 2013 Curriculum formulation is to form students who have noble attitudes, values and character by instilling and implementing character education in all subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, in essence this curriculum emphasizes the achievement of scientific attitudes and student character. Because the success of learning in school is not only based on cognitive aspects, but also must be viewed from the aspect of attitude (Marini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%